Study of hydraulic characteristics of trapezoidal piano key side weir using different approaches - Kilic, Zeyneb; Emiroglu, M. Emin (Iwa Publishing, 2022)
Side weirs are widely used in hydraulic engineering applications. The studies on the subject have been generally focused on classical and labyrinth side weirs. However, the same is not true for piano key side weirs (PKSW) in a straight channel. The piano key weir (PKW) has high discharge capacity compared with classical weirs. In this study, the hydraulic characteristics of a trapezoidal piano key side weir (TPKSW) in straight channels were investigated experimentally. In all experiments, the hydraulic characteristics of nine TPKSW models were studied extensively using the De Marchi, Dominguez and Schmidt approaches in the subcritical flow regime, with Froude number range 0.12 < F-1 < 0.87. The results show that a TPKSW provides better performance compared to traditional rectangular and triangular labyrinth side weirs. Specifically, for the 0.12 < F-1 < 0.4 condition, the efficiencies of a TPKSW and trapezoidal labyrinth side weir are close to each other. A trapezoidal labyrinth side weir is more efficient than a TPKSW at larger Froude numbers. The discharge capacity of the TPKSW is 2.9 to 12 times higher than that of the rectangular side weir. Scatter diagrams were obtained for C-PW and F-1 numbers using various approaches available in the literature. The diagram generated by the De Marchi approach has much less scattering, compared to the diagrams generated by the Dominguez and Schmidt approaches. It has been determined that TPKSWs are an effective type of side weir in lateral flows. Lastly, an empirical equation was obtained for the discharge coefficient, which is in good agreement with the experimental data.
Keywords: discharge coefficient; open-channel flow; piano key weir; side weir; water discharge